The Relationship Between Family Function and The Incidence Of Postpartum Blues In Postpartum Mothers - ayu, sekar (Poltekkes Kemenkes Semarang, 2024)
ABSTRACT Background: Postpartum blues are sadness and depression experienced by mothers after giving birth. There are two factors that cause postpartum blues, namely internal and external factors. One of the external factors that causes postpartum blues is family function. The function of the family is important in ensuring the condition of the postpartum in the physical, social anda spiritual aspects so that she can develop properly. The impact of postpartum blues can cause mothers to experience recurring illnesses as well as the impact on the role of a mother in the emotional development and behaviour of children, as well as the role of the mother in the family. Research Objective : To determine the relationship between family function and the incidence of postpartum blues in postpartum mothers at PKU Muhammadiyah Bantul Hospital. Method : The research design used in this study was cross sectional. The study sample amounted to 38 respondents of postpartum mothers with purposive sampling sample techniques. The study data was collected using the APGAR Family questionnaire to measure family functioning and the Edinburhg Postantal Depression Scale (EPDS) to measure the incidence of postpartum blues. The statistical tests used were univariate and bivariate analysis using the fisher’s exact tests. Results : The results showed that the majority of family functions were in the moderate dysfunctional category (68.4%) and the majority who experienced postpartum blues events (71.1%). The measurement results were tested using fisher’s exact test and obtained p value = 0.000. Conclusion : There is a significant relationship between family function and the incidence of postpartum blues in postpartum mothers at PKU Muhammadiyah Bantul Hospital. Keywords : Family Function, Postpartum Blues, Postpartum